Needs Analysis for Informatics Engineering Students as a Basis to Develop Teaching Materials on English for Specific Purposes - Kadek Yogi Susana; Agus Ari Iswara (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This research aims is to find and describe students' needs for ESP and find out students' perceptions of ESP teaching that has been running. This research is a descriptive research with a qualitative approach. The subject of this research was the first semester students of Informatics Engineering of STMIK STIKOM Indonesia. The data collection was done using online questionnaire on google form application. The data obtained were then classified so that the needs of Informatics Engineering students on English learning can be identified and then be described. The results of this research can be used as a reference for subsequent research, namely syllabus planning and the development of teaching materials of ESP. Referring to students awareness of the importance of speaking skill and the also the need of having grammar lessons as basis for their practical competence, it is a task for ESP lecturer to apply teaching strategies which are interesting, motivating and engaging to cover both areas in equal portion.